2015
DOI: 10.1186/1476-511x-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe ameliorates atherogenic lipids profiles, insulin resistance and hepatocyte growth factor in obese patients with hypercholesterolemia

Abstract: BackgroundEzetimibe ameliorates serum low-density lipoprotein cholesterol (LDL-c) and it has been approved for the treatment of hypercholesterolemia. However, the effects of ezetimibe on specific biomarkers have not been fully clarified in obese Japanese patients.MethodsA total of 101 patients (47 males and 54 females) were registered in this study during 2011 and 2012. All patients were over 20 years old, were obese [body mass index (BMI) ≥ 25kg/m2] and had hypercholesterolemia (LDL-c ≥ 120mg/dl). After exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 33 publications
4
82
1
Order By: Relevance
“…Several studies have reported an effect of statins on glucose metabolism [23,[31][32][33][34] and on the risk of new-onset diabetes [35,36], but the results remain controversial. Results from earlier studies also suggest that ezetimibe could improve insulin resistance [37][38][39]. Two studies reported that the addition of ezetimibe to a statin as combination therapy improved insulin resistance and did not increase the risk of diabetes [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported an effect of statins on glucose metabolism [23,[31][32][33][34] and on the risk of new-onset diabetes [35,36], but the results remain controversial. Results from earlier studies also suggest that ezetimibe could improve insulin resistance [37][38][39]. Two studies reported that the addition of ezetimibe to a statin as combination therapy improved insulin resistance and did not increase the risk of diabetes [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…It has also been shown in humans that adopting a Nordic diet (which includes high fish consumption), leads to reduction in some plasma CER[ NS ] ceramides, although the originating tissue of these species is unknown [66]. This variation between tissue responses is evident within the same animal, as mice on fish oil- or krill oil-supplemented diets had decreased CER[ NS ] and CER[ NDS ] ceramides in the liver, and increased CER[ NS ] and CER[ NDS ] ceramides in the brain [67]. Increased ceramide production has also been seen in breast cancer cells following EPA or DHA supplementation in vitro , or fish oil supplementation in vivo , through increased neutral sphingomyelinase activity [68].…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipolysis in adipose tissue and increased plasma free fatty acids together with metaflammation are believed to promote lipid accumulation in hepatocytes leading to liver steatosis[27,28]. The pathogenesis of fibrotic NASH is described in a “two-hit hypothesis”, wherein insulin resistance acts as “first hit” that leads to liver steatosis which renders hepatocytes more susceptible to a “second hit” which could involve inflammatory and oxidative stress mediators, lipotoxic fatty acids, cholesterol and ceramides[29].…”
Section: Pathogenesis Of Nashmentioning
confidence: 99%